The ultimate treat? Young Israeli children's media use under their grandparents' care. Issue 4 (2nd October 2019) - Elias, Nelly; Nimrod, Galit; Lemish, Dafna
ABSTRACT: A substantial effort was made over the years to reveal predictors of children's screen time in an attempt to suggest effective ways to minimize its negative effects. Studies were mostly based on parents' reports and ignored other major caregivers, particularly grandparents. Accordingly, this study offers a pioneer exploration of young children's interactive and non-interactive media use under their grandparent's care and the factors associated with extensive use. The study was based on an online survey of 356 grandparents of children aged 2–7, who reported taking care of their grandchildren at least once a week. The study shows that children spend about half of the time under their grandparents' watch using various media. Use time increased with age and was higher among boys compared to girls. Non-interactive media use was explained by place and duration of care, number of parents' instructions, bringing a mobile device to the grandparent's home, having the television on in the background, and grandparents' mediation efforts. Interactive media use was explained by duration of care and grandparent's sex, with male grandparents contributing to longer use. These findings raise concerns regarding young children's media use under their grandparents' watch, but also suggest effective strategies for its reduction.